Predicting Factors of Caregiving Burden among Caregivers of Persons with Schizophrenia - Jansai, Anothai; Bhatarasakoon, Patraporn; Skulphan, Sombat; Suvanayos, Chalinee (Journal of Phrapokklao Nursing College, Chanthaburi, 2024)
This predictive correlational research aimed to investigate caregiving burden and predicting factors of caregiving burden among caregivers of persons with schizophrenia. The samples were 110 caregivers of persons with schizophrenia who had come to receive services at the psychiatric clinic of the district hospitals in Chiang Mai Province. The research instruments included a caregiver demographic data questionnaire, the Brief Psychiatric Rating Scale (BPRS) with a reliability of .83, a caregiving knowledge test with a reliability of .84, a social support questionnaire with a reliability of .88, a psychiatric family caregiving skills scale with a reliability of .84, and the Zarit Burden Interview (ZBI) with a reliability of .83. Data were collected from June to August 2021. Statistics used for data analysis included frequency, percentage, mean, standard deviation, and stepwise multiple regression analysis. The research results revealed that most caregivers of persons with schizophrenia perceived no caregiving burden (63.64%). Caregiving knowledge could statistically significantly predict the caregiving burden among caregivers of persons with schizophrenia which accounted for 10.60% (R2 = .106, p < .01). This research suggests that healthcare providers should assess caregiving burden among caregivers of persons with schizophrenia as well as appropriately provide caregiving knowledge in order to decrease the perception of the caregiving burden.